ANALISIS PENGARUH PEMBINAAN ETIKA PROFESI DAN LINGKUNGAN SOSIAL TERHADAP INTEGRITAS PRAJA (IPDN KAMPUS SULAWESI SELATAN) - Abudzar Galigo (Program Pascasarjana Universitas Garut, 2026)
This study aims to analyze the influence of professional ethics development and the social environment on the integrity of civil servants at the IPDN South Sulawesi Campus. The research method used is a quantitative approach with Partial Least Square (PLS) analysis technique. The research sample consisted of active civil servants selected through a proportional sampling technique. The results of the study indicate that partially professional ethics development does not have a significant effect on civil servant integrity. This finding indicates that the professional ethics development that has been carried out so far has not been able to effectively encourage the formation of integrity behavior in civil servants. Conversely, the results of the study show that the social environment has a positive and significant effect on civil servant integrity. This finding indicates that efforts to foster integrity are not sufficient through a formal approach, but must be directed at establishing a consistent social culture and real role models. Simultaneously, professional ethics development and the social environment have a significant effect on civil servant integrity, although the largest contribution comes from the social environment variable. This finding emphasizes the importance of an integrative approach in civil servant character development, which not only emphasizes normative aspects through professional ethics, but also strengthens the social ecosystem that supports the internalization of moral values. This study has implications for the need to evaluate ethical development policies and strengthen a positive social culture in the civil service education environment.